Deviant Citizenship Behavior: A Comprehensive Framework towards Behavioral Excellence in Organizations - Dhiman Chowdhury (The East Asian Journal of Business Management, 2015)
Purpose – While studying the topic of seeking behavioral excellence (proactive and creative competence) in organization, scholars have presented a variety of literature sprinkled with countless theories on behavioral competence. Research design, data, and methodology - Foremost among the several theories on this topic are two distinct sets of behav-ioral theories: OCB (Organizational Citizenship Behavior) and Constructive Deviance. Both of these theories attempt to posit their usefulness in positive organizational outcomes (such as organizational effectiveness, quality, performance, and innovations). Results - However, their proposed constructs are opposing and studies are conducted in isolation, thereby creating a sigificant literature gap and omitting the possibility of being inclusive of the best that both OCB and constructive deviance have to offer. Conclusions - The article bridges the gap by critically examining OCB and constructive deviance and including a consideration of other empirical studies in an attempt to be comprehensive while, at the same time, seeking to find an effective behavioral construct that is both appropriate and conducive for positive organizational outcomes in the context of the current business environment.
Keywords: 330; Organizational Behavior; Organizational Citizenship Behavior; Constructive Deviance; Innovation; Innovative Work Behavior; Organizational Innovation